Indenofluorenes and Quinoidal Analogues – A New Class of Electron-Accepting Materials - Michael, Haley (My University, 2017)
This talk will present our synthetic, structural and materials studies of a new class of electron-accepting molecules based on the indenofluorene (IF) skeleton. The initial preparative route involved transannular cyclization of octadehydrodibenzo[12]annulenes to afford the pentacyclic ring system. Subsequent transformations generated the first stable examples of the fully conjugated, 20 pi-electron, formally anti-aromatic compounds.[1] Optimization of intermediate IF-6,12-dione synthesis via a simple three-step process now permits access to IF derivatives in multigram quantities.[2] Work on 6,12-diarylIFs demonstrated that single crystals of the pentafluorophenyl derivative could serve as an active layer in organic field effect transistors (OFETs) that exhibit ambipolar behavior using Au source/drain contacts.[3] Current studies are focused on varying the antiaromaticity of the indacene unit by replacement of the benzene groups with thiophene units[4] as well as increasing biradical character of the framework by expansion of the quinoidal core.[5] [1] Chase, D. T.; Rose, B. D.; McClintock, S. P.; Zakharov, L. N.; Haley, M. M. Angew. Chem. Int. Ed. 2011, 50, 1127. [2] Chase, D. T.; Fix, A. G.; Rose, B. D.; Weber, C. D.; Nobusue, S.; Stockwell, C. E.; Zakharov, L. N.; Lonergan, M. C.; Haley, M. M. Angew. Chem. Int. Ed. 2011, 50, 11103. [3] Chase, D. T.; Fix, A. G.; Kang, S. J.; Rose, B. D.; Weber, C. D.; Zhong, Y.; Zakharov, L. N.; Lonergan, M. C.; Nuckolls, C.; Haley, M. M. J. Am. Chem. Soc. 2012, 134, 10349. [4] (a) Young, B. S.; Chase, D. T.; Marshall, J. L.; Vonnegut, C. L.; Zakharov, L. N.; Haley, M. M. Chem. Sci. 2014, 5, 1008; (b) Marshall, J. L.; Uchida, K.; Frederickson, C. K.; Schütt, C.; Zeidell, A. M.; Goetz, K. P.; Finn, T. W.; Jarolimek, K.; Zakharov, L. N.; Risko, C.; Herges, R.; Jurchescu, O. D.; Haley, M. M., Chem. Sci. 2016, 7, 5547. [5] (a) Rudebusch, G. E.; Fix, A. G.; Henthorn, H. A.; Vonnegut, C. L.; Zakharov, L. N.; Haley, M. M. Chem. Sci. 2014, 5, 3627; (b) Rudebusch, G. E.; Zafra, J. L.; Jorner, K.; Fukuda, K.; Marshall, J. L.; Arrechea-Marcos, I.; Espejo, G. L.; Ponce-Ortiz, R.; Gomez-Garcia, C. J.; Zakharov, L. N.; Nakano, M.; Ottosson, H.; Casado, J.; Haley, M. M. Nature Chem. 2016, 8, 753.
Indenoindacenes. Physical properties and challengues
Keywords: Química física; Organic Materials; Indenoacene; Electron accepting; Ambipolar